Mitochondria and diabetes: An intriguing pathogenetic role - Newsholme, Philip; Gaudel, C.; Krause, M. (Springer New York LLC, 2012)
Mitochondria play a key role in energy metabolism and ATP production in many tissues, including skeletal muscle, cardiac muscle, brain and liver. Inherent disorders of mitochondria such as mDNA deletions cause major disruption of metabolism and can result in severe disease phenotypes. However, the incidence of such mDNA based disorders is extremely rare and cannot account for the dramatic rise in human metabolic diseases, which are characterised by defects in energy metabolism. Mitochondrial dysfunction characterised by reduced ATP generation and reduced mitochondrial number in skeletal muscle or reduced ATP generation and mitochondrial stimulus-secretion coupling in the pancreatic beta cell has been implicated in the pathology of chronic metabolic disease associated with type 2 diabetes mellitus and also with aging. Additionally the generation of ROS from mitochondria and other cellular sources may interfere in insulin signaling in muscle, contributing to insulin resistance. Reduced mitochondrial oxidative capacity coupled with increased ROS generation underlies the accumulation of intramuscular fat, insulin resistance and muscle dysfunction in aging. We will review the molecular basis for optimal mitochondrial function or mechanisms of dysfunction and correlate with pathology of identified diseases and aging.